PENINGKATAN AKTIFITAS BELAJAR PEMROGRAMAN VISUAL BERBASIS DESKTOP MELALUI PEMANFAATAN ALAT PERAGA PROGAM APLIKASI INVENTARIS BAGI SISWA SMK NEGERI 5 SURAKARTA - Basori, Basori; Khusnawan, Dona Asm’ul (Jurnal Ilmiah Pendidikan Teknik dan Kejuruan, 2014)
The background of this study is the lack of students activity in the conventional learning on desktopbasedvisual programming subjects. As a result, many students do not understand the material provided by theteacher. The purpose of this study is to determine the enhancement in the learning activity of student byutilizing props inventory application program for students of SMK Negeri 5 Surakarta.The research was conducted by using class action research with 2 cycles. The subject of study taken isthe class XI RPL A in SMK Negeri 5 Surakarta. The research object is the quality of the learning process, ie theactivity of learning. The experiment was conducted on 2nd semester academic year 2013/2014. The datacollection techniques used were observation and interviews. The Data analysis technique using the qualitativeanalysis refers to the analysis model Miles and Huberman.Based on the result of the research , we can conclude that an increase in the learning activity of precyclestudent learning is 34,43%, in cycle 1 is 71,65%, and increased to 77,04% in cycle 2. It is proved that theprops inventory application program helps students to increase the learning activity on a desktop-based visualprogramming subject .